Elevated concentrations of cardiac troponin T are associated with thoracic aortic calcification in non-dialysis chronic kidney disease patients of stage G3 to G5 - Wenjiao Zhu; Zhiman Lai; Miaorong Xue; Shaozhen Feng; Pinning Feng; Xiantian Pan; Xiaojie Ke; Xionghui Chen; Zhijian Li; Haiping Mao; Xiao Yang; Fengxian Huang; et al. (Renal Failure)
Background Vascular calcification (VC), especially coronary artery calcification (CAC), serves as a robust predictor of cardiovascular mortality in chronic kidney disease (CKD) patients. Recent studies have revealed that the presence of extra-coronary calcifications (ECCs) contributes to cardiovascular disease (CVD). Elevated myocardial injury markers predict mortality risk in CKD patients and are associated with CVD. Nevertheless, the relationship between VC, including CAC and ECCs, and myocardial injury markers remain unexplored in non-dialysis CKD patients.Methods In 278 non-dialysis CKD patients of stage G3 to G5, we assessed calcified scores in CAC (Agatston score) and ECCs including thoracic aortic calcification (TAC), abdominal aortic calcification (AAC), carotid artery calcification, and valvular calcification. We analyzed the relationships between VC and myocardial injury markers of cardiac troponin T (cTnT) and creatine kinase-MB (CK-MB).Results A total of 278 non-dialysis CKD patients (median age 52.4 ± 13.2; male 65.1%; diabetes 33.5%) were enrolled. A total of 71.8% (227) of patients had cTnT levels above the upper limit of normal (> 0.014 ng/mL). Moderate to severe (calcified score ≥100 vs. <100), CAC (OR 6.39; 95% CI 1.03–39.61) and TAC (OR 6.16; 95% CI 1.76–21.55) were significantly associated with higher cTnT concentrations after adjustment for confounders. Additionally, male sex and a lower eGFR were also associated with cTnT elevation. However, when we included CAC and TAC in one model, only moderate to severe TAC (OR 4.85; 95% CI 1.38–16.96) was a risk factor for cTnT elevation, but not CAC. Furthermore, patients with severer TAC presented lower diastolic blood pressure (DBP), wider pulse pressure (p < 0.001) and higher prevalence of left ventricular hypertrophy (LVH).Conclusion Moderate to severe thoracic aortic calcification (TAC score ≥ 100) is significantly associated with elevated cTnT concentrations in non-dialysis CKD patients of stage G3 to G5. The linkage may result from decreased coronary perfusion and relative myocardial ischemia.